2010
DOI: 10.1007/s10661-009-1283-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of transport and industrial emissions on the ambient air quality of Lahore City, Pakistan

Abstract: Lahore's population is growing at a rate of 4% a year. It is widely perceived that because of this rapid growth, the level of services provided to the city's 7 million inhabitants has substantially deteriorated. This study presents the finding of ambient air quality monitoring carried out in Lahore City, Pakistan. The ambient air quality was monitored for criteria pollutants carbon monoxide (CO), nitrogen dioxide (NO(2)), sulfur dioxide (SO(2)), ozone (O(3)), particulate matter (TSP and PM(10)), lead (Pb), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…The literature under this study identified that Lahore is the most highly studied city regarding air pollution monitoring and investigation [8,9,11,14,21,32,34,40,[43][44][45][46], followed by Islamabad [2,10,12,17,35,[47][48][49][50][51][52], Karachi [38,39,41,44,53], Peshawar [18,44], Quetta [7], Faisalabad [3], Swat [16], and Wah [13]. A countrywide study pertaining to atmospheric emission was also undertaken by Shahid [15], to investigate seasonal variations of aerosols (sulfate, nitrate, ammonium, organic carbon, black carbon, and PM 2.5 ), and its contributions towards domestic anthropogenic and transboundary transport emissions.…”
Section: Air Quality and Atmospheric Pollution In Pakistan: A Brief Lmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature under this study identified that Lahore is the most highly studied city regarding air pollution monitoring and investigation [8,9,11,14,21,32,34,40,[43][44][45][46], followed by Islamabad [2,10,12,17,35,[47][48][49][50][51][52], Karachi [38,39,41,44,53], Peshawar [18,44], Quetta [7], Faisalabad [3], Swat [16], and Wah [13]. A countrywide study pertaining to atmospheric emission was also undertaken by Shahid [15], to investigate seasonal variations of aerosols (sulfate, nitrate, ammonium, organic carbon, black carbon, and PM 2.5 ), and its contributions towards domestic anthropogenic and transboundary transport emissions.…”
Section: Air Quality and Atmospheric Pollution In Pakistan: A Brief Lmentioning
confidence: 99%
“…Moreover, PM is a highly reactive substance and provides a surface area for various heavy metals, thus raising another major concern of inferior air quality and human health [9,12]. Other forms of major atmospheric aerosols species include sulfate (SO 4 2− ), nitrate (NO 3− ), ammonium (NH 4 + ), black carbon (BC), and organic carbon (OC) [13,14]. It has been reported that the concentrations of PM, SO 2 , CO, NO 2 , and Pb in various cities across Pakistan have surpassed the safer limits defined by WHO, except for the O 3 concentration, which is within the WHO limits [1].…”
Section: Introductionmentioning
confidence: 99%
“…Salam et al (2003) determined trace elements in Dhaka Bangladesh and found that Fe (24800 ng m ) and Zn (3020 ng m -3 ) in PM 10 samples collected from an urban site in Lahore. Ali and Athar (2010) monitored the ambient air quality of Lahore and determined PM10 and Pb levels. The concentration of Pb at different locations of the city was found in the range of 1900 to 7200 ng m -3…”
Section: Trace Elementsmentioning
confidence: 99%
“…During last few years, Lahore is engulfed by a disturbing of air quality due to rapid industrial development and urbanization. Increase in number of industries and automobiles, deforestation and crop burnings contributed to this alarming situation in Lahore [4]. Increase in population leads towards the decrease in the natural sources [5].…”
Section: Introductionmentioning
confidence: 99%